USAHA PELESTARIAN DAN PERLINDUNGAN KALI MEWEK, KOTA MALANG DALAM RANGKA PENGELOLAAN DAERAH ALIRAN SUNGAI - Mochamad Awaludin Adam; Maftuch . (Journal of Environmental Engineering and Sustainable Technology, 2014)
Conservation and preservation of the waters environment of needed, in order to protect the flow of river water to downstream areas. Waters often contaminated and carried out the destruction by human activity itself. The threatens of existence of the flow of Kali Mewek. Kali Mewek of the flow needed some special handling related to the preservation river a worth, because of the cluster housing developmented. Activities that need to be done to efforts the preservation and protection is operation and maintenance river a worth; and the conservation, development water allocation, water quality control and ecotourism.